A meta-analysis of the impact of trust on technology acceptance model: Investigation of moderating influence of subject and context type - Wu, Kewen; Zhao, Yuxiang; Zhu, Qinghua; Tan, Xiaojie; Zheng, Hua (International journal of information management, 2011)
► Direct effect analysis suggests trust is an important variable influences IT adoption. ► Effect sizes of relationships are high when studies conduct in commercial setting. ► Effect sizes of relationships are high when studies conduct in student setting. ► Suggestions are given to both researchers and service providers. The technology acceptance model (TAM) has proven to be one of the most powerful theories to explain user's technology adoption. Among many external variables incorporated into TAM, trust is considered to be an important factor that influences the user's online behavior, especially in the e-commerce context. This study conducts a meta-analysis based on the previous TAM studies in an attempt to make well-grounded statements on the role of trust. Furthermore, the paper examines those TAM studies by considering moderating effects of subject type (students or non-students) and context type (commercial or non-commercial). Results indicate a significant influence of trust on TAM constructs. Moderating effects are found for most pair-wise relationships. The findings yield implications for both researchers and service providers.